2021
DOI: 10.1126/sciadv.abg9518
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages orchestrate the expansion of a proangiogenic perivascular niche during cancer progression

Abstract: Perivascular macrophages orchestrate the expansion of pericyte-like mesenchymal cells to create a proangiogenic niche in cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 86 publications
(122 reference statements)
4
67
0
Order By: Relevance
“…One subset of TAMs reside in close proximity to blood vasculature (<15-20 µm) (14)(15)(16) and are termed perivascular TAMs (PvTAMs). PvTAMs support a variety of pro-tumoral functions including neo-angiogenesis (15,16), metastasis (3,17,18) and facilitate tumor recurrence post chemotherapy (19). Recently, we demonstrated that a subset of PvTAMs expressing lymphatic vessel endothelial hyaluronan receptor 1 (Lyve-1) form a pro-angiogenic Pv niche with a population of pericyte-like cancer associated fibroblasts (CAFs) and orchestrate the platelet-derived growth factor-C (PDGF-C)-dependent expansion of the CAF population with the growing tumor (16).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…One subset of TAMs reside in close proximity to blood vasculature (<15-20 µm) (14)(15)(16) and are termed perivascular TAMs (PvTAMs). PvTAMs support a variety of pro-tumoral functions including neo-angiogenesis (15,16), metastasis (3,17,18) and facilitate tumor recurrence post chemotherapy (19). Recently, we demonstrated that a subset of PvTAMs expressing lymphatic vessel endothelial hyaluronan receptor 1 (Lyve-1) form a pro-angiogenic Pv niche with a population of pericyte-like cancer associated fibroblasts (CAFs) and orchestrate the platelet-derived growth factor-C (PDGF-C)-dependent expansion of the CAF population with the growing tumor (16).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that a subset of PvTAMs expressing lymphatic vessel endothelial hyaluronan receptor 1 (Lyve-1) form a pro-angiogenic Pv niche with a population of pericyte-like cancer associated fibroblasts (CAFs) and orchestrate the platelet-derived growth factor-C (PDGF-C)-dependent expansion of the CAF population with the growing tumor (16). Lyve-1 was traditionally considered a marker of lymphatic endothelium (20), but has emerged as selective marker for a sub-population of Pv tissue-resident macrophages (21)(22)(23)(24)(25) and TAMs (16,26). Depleting Lyve-1 + PvTAMs in the spontaneous mouse mammary tumor virus polyomavirus middle T antigen (MMTV-PyMT) murine model of breast cancer using liposome-based approaches resulted in tumor control, highlighting the importance of the TAM subset in cancer progression and formation of the Pv niche (16).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations